OC-8 Use of new psychoactive drugs by hiv-infected women and its' impact on mother-to-child hiv transmission in romania. (6th June 2017) - Mardarescu, Mariana; Petre, Cristina; Teodora, Constantin Andreea; Iancu, Marieta; Cibea, Alina; Draghicenoiu, Ruxandra; Ungurianu, Rodica; Tudor, Ana Maria; Vlad, Delia; Petrea, Sorin; Matei, Carina; Otelea, Dan; et al.
Abstract : Background and aims: The national antenatal HIV screening process in Romania revealed an increase in the number of HIV infected women-IDUs since 2011, due to the use of synthetic cannabinoids and cathinones, or "legal highs". Moreover, the percentage of new IDU/HIV cases increased from 2.8% in 2010 to 20% in 2015, most of them living in or around Bucharest. The aim of the surveillance was to have a more accurate view on the drug-using HIV infected mothers and the effect of this phenomenon on their babies. Methods: Between January 2012 and December 2016, the Paediatric Immunosuppression Unit of INBI "Prof. Dr. Matei Bals" surveyed 468 HIV-exposed newborns. 13, 46% (63/468) were perinatally exposed to "new drugs". However, at the end of 2015 the rate of HIV mother-to-child transmission in Romania remained stable- below 2.3%. The following parameters were evaluated for mothers: time of HIV screening, time of HIV diagnosis, age, prenatal care, time when taken into active surveillance, treatment/prophylaxis, type of birth, drugs taken and screening for co-infections (HBV, HCV, STIs). For children we focused on: sex, age, time of diagnosis, ART prophylaxis, type of birth, feeding, neurological assessment, CD4 count, HIV-RNA, ultrasound evaluation. Results: During the 4 year monitoring period, the following results of HIV time of detection in IDU/HIV mothers were obtained: 41.26% (26/63 mothers tested) were found with HIV before pregnancy, 11.1% (7/63) during pregnancy, 41.26% (26/63 ) during delivery and 6.34 % (4/63) in the first 24 hours after birth. Although all newborns perinatally exposed to HIV/IDU benefitted from post partum prophylaxis and received artificial nutrition, 14.2 % (9 /63) exposed to drug use were HIV infected. All children had poor neonatal adaption, mainly severe withdrawal syndrome – 63.49% (40/63) of newborns monitored and more than 50% had neurological lesions. Conclusions: Most drug-using HIV infected pregnant women have little access to antenatal care, which leads to late detection of HIV. The use of synthetic cannabinoids and cathinones by these women has significant effects on newborns and their subsequent development which is a challenge for the post-?partum surveillance system. These women come from poor families who don't ensure them a proper support. Furthermore, due to issues associated to risky behaviour it is difficult to include them in HIV screening or prevention programmes, which need to be adapted to their needs.